Social Media Marketing pada Etienne Space - Wongsodiredjo, Jacklyn; Teguh, Monika (Journal of Management and Bussines (JOMB), 2024)
This research aims to analyze the implementation of Etienne Space's social media marketing and its impact on increasing engagement on Instagram and TikTok social media accounts. The method used in this research uses a qualitative approach. The results showed that the implementation of marketing strategies with 4C digital business communication elements (Context, Communication, Collaboration, and Connection) through content marketing and influencer marketing strategies that implement by using narratives that focus on virality, collaboration with local influencers, and personal interaction through comment responses and direct messages had a significant impact in increasing audience engagement and interest. The implementation of this strategy also succeeded in creating an Electronic Word-of-Mouth (eWOM) effect, which supported the visibility of Etienne Space and encouraged the growth of new customers. Etienne Space's implementation of social media marketing strategies has been successful in increasing brand visibility and engagement, which has resulted in business growth. Keywords: Context, Communication, Collaboration, Social Media Marketing